The Biochemical Analysis and Characterization of Strobilanthes ciliatus Nees (Bremek): Leaf Extracts - Vasanth Nayagam; Tamil mullai Selvaraj; Joelri Michael Raj Lourdhurajan; Anthony Samy; Savarimuthu Ignacimuthu; Dons Thiraviadoss (Journal of Stress Physiology & Biochemistry, 2023)
The present study was aimed to analysis and characterizes the biochemical elements of Strobilanthes ciliatus Nees leaf extract. The healthy leaves of S. ciliatus were collected and the plant extracts were prepared as dried powder. Biochemical analysis was conducted using standard procedures for the leaf extracts. The various analysis and charecterization of S.ciliatus was determined via total chlorophyll content. The results have envisaged that plant extract have significantly with a presence of bio compounds. The present study shows S. ciliatus to be an important medicinal plant, since the leaves showed good biochemical activity. Thus, it may use in the treatment of diseases and may also use in the preparation of natural or herbal drugs due to the presence of biochemical.